Contribuição ao projeto de elementos estruturais de concreto armado com descontinuidades através do Modelo de Painéis Enrijecidos - Silva, João Gilberto Teixeira (2004)
The traditional beam theory cannot be applied to study walls, corbels and regions with holes or change of inertia, because the Navier-Bernoulli s hypothesis cannot be used to these cases. Procedures based in the plates theories, the finite element method or truss-and-tie method are often used to study these type of reinforced concrete structures. In this work, an alternative procedure that joins the advantages of truss-and-tie method and finite element method is used to design the above mentioned types of reinforced concrete structures. Using this procedure, called Stringer and panel model, the structures are modeled as a group of panels with their edges stiffened by straight bars (stringers). It s supposed that the stringers transmit only axial forces, while the panels, transmit only shear forces. The analyses can be made considering the distribution of elastic stresses, called linear analysis, or considering the redistribution of stresses due to the concrete crack. Examples are analyzed, and the results for the reinforcement are compared with the other results obtained by the use of other methods. Element size effects on the reinforcement volume are analyzed and the theoretical load-displacement curves are compared with the corresponding experimental load-displacement curves. Finally, comparison between the reinforcement volumes obtained by the linear analysis and by the non linear analysis is made.